2012
DOI: 10.1371/annotation/6841c4e1-58e6-4412-9b71-bd6bc8bbe549
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Epizootic Emergence of Usutu Virus in Wild and Captive Birds in Germany

Abstract: This study aimed to identify the causative agent of mass mortality in wild and captive birds in southwest Germany and to gather insights into the phylogenetic relationship and spatial distribution of the pathogen. Since June 2011, 223 dead birds were collected and tested for the presence of viral pathogens. Usutu virus (USUV) RNA was detected by real-time RT-PCR in 86 birds representing 6 species. The virus was isolated in cell culture from the heart of 18 Blackbirds (Turdus merula). USUVspecific antigen was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Requests for the submission of dead birds were made via press releases of involved institutes and subsequent dissemination of the information by different kinds of media, including newspaper articles, television and radio. Total RNA from homogenized tissue samples (brain, liver, lung, or heart) was extracted and analyzed for the presence of flavivirus RNA by using a modified pan-flavivirus reverse transcription PCR [15] or WNV-specific reverse transcription quantitative PCR (RT-qPCR) [16]. Furthermore, all samples were also tested using the USUV-specific RT-qPCR described by Jöst et al [17] (data not shown).…”
Section: Wnv Screening Of Birds Horses and Mosquitoesmentioning
confidence: 99%
“…Requests for the submission of dead birds were made via press releases of involved institutes and subsequent dissemination of the information by different kinds of media, including newspaper articles, television and radio. Total RNA from homogenized tissue samples (brain, liver, lung, or heart) was extracted and analyzed for the presence of flavivirus RNA by using a modified pan-flavivirus reverse transcription PCR [15] or WNV-specific reverse transcription quantitative PCR (RT-qPCR) [16]. Furthermore, all samples were also tested using the USUV-specific RT-qPCR described by Jöst et al [17] (data not shown).…”
Section: Wnv Screening Of Birds Horses and Mosquitoesmentioning
confidence: 99%
“…Virus ribonucleic acid was also detected in Israel in Culex mosquitoes collected in 2014-2015 [33]. USUV can be responsible for high mortalities in wild birds, especially blackbirds (Turdus merula) and captive birds belonging to the order Strigiformes (e.g., Strix nebulosa, Strix aluco, Bubo scandiacus) [24,34]. USUV is also a zoonotic virus.…”
Section: Introductionmentioning
confidence: 98%
“…At least 99 European bird species, belonging to 36 different families [13][14][15][16], are currently known to be susceptible to USUV infection. However, only in a few of these avian species a fatal disease linked to USUV has been described [17], including the European blackbird (Turdus merula) [15,[18][19][20][21], house sparrow (Passer domesticus) [22,23], grey owl (Strix nebulosa) [24], and common scoter (Melanitta nigra) [14]. The reasons for this selective pathogenicity are, still, unknown and avian models are critically needed to study the pathogenesis, transmission routes, and virulence of USUV.…”
Section: Introductionmentioning
confidence: 99%
“…Further, canaries are considered as an excellent model of infection by WNV [28]. Epidemiological surveys carried out in Germany during the period between 2011 and 2013 and during 2017-2018 detected USUV genomic RNA in these birds, indicating that they can be naturally infected with the virus [19,29,30]. However, whether USUV can be pathogenic for this species is still unknown.…”
Section: Introductionmentioning
confidence: 99%